Evaluation of response after pre-operative radiotherapy in soft tissue sarcomas; the European Organisation for Research and Treatment of Cancer – Soft Tissue and Bone Sarcoma Group (EORTC – STBSG) and Imaging Group recommendations for radiological examination and reporting with an emphasis on magnetic resonance imaging. (March 2016) - Messiou, C.; Bonvalot, S.; Gronchi, A.; Vanel, D.; Meyer, M.; Robinson, P.; Morosi, C.; Bloem, J.L.; Terrier, P.H.; Lazar, A.; Le Péchoux, C.; Wardelman, E.; et al.
Abstract: At present, there is no standardised approach for the radiological evaluation of soft tissue sarcomas following radiotherapy (RT). This manuscript, produced by a European Organisation for Research and Treatment of Cancer – Soft Tissue and Bone Sarcoma Group (EORTC – STBSG) and Imaging Group endorsed task force, aims to propose standardisation of magnetic resonance imaging techniques and interpretation after neoadjuvant RT for routine use and within clinical trials.